Measuring the non-observed economy : a handbook - Organisation for Economic Co-operation and Development. Statistics Directorate; International Monetary Fund. Bureau of Statistics; International Labour Organisation. Bureau of Statistics; Commonwealth of Independent States. Statistical Committee (Paris, France : OECD, 2002)
This essential Handbook makes underground, hidden, grey economies intelligible and consistently quantifiable. An invaluable tool for statistics producers and users and researchers, the book explains how the non-observed economy can be measured and comments on the reliability of and differences between various methods. The purpose of this Handbook is to identify and promote best practice consistent with international standards like the 1993 System of National Accounts.
Foreword and Acknowledgements; Table of Contents; Abbreviations and Acronyms; Chapter 1. Introduction; Chapter 2. Conceptual Framework; Chapter 3. Notions of the Non-Observed Economy; Chapter 4. Assessment of National Accounts; Chapter 5. National Accounts Methods to Achieve Exhaustiveness; Chapter 6. Assessment and Improvement of Data Collection Programme; Chapter 7. Implementation Strategy; Chapter 8. Underground Production; Chapter 9. Illegal Production; Chapter 10. Informal Sector Production; Chapter 11. Household Production for Own final Use; Chapter 12. Macro-model Methods; Annexes
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Informal sector (Economics) -- Statistics; Secteur informel (Économie politique) -- Statistiques; BUSINESS & ECONOMICS -- Economics -- General; BUSINESS & ECONOMICS -- Reference; Méthodes statistiques; Manuels; Organisation de coopération et de développement économiques.; Economie souterraine; Comptes nationaux; Informal sector (Economics); Erhebungsverfahren; Schattenwirtschaft; Datenerhebung; Informele economie; Meetmethoden; Statistics